Pembuatan Simplisia dan Teknik Penyiapan Obat Tradisional Jahe Merah dan Daun Pepaya untuk Standardisasi Dosis - Maya Dian Rakhmawatie; Nanik Marfu'ati (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2023)
Many Family Welfare Empowerment Groups (PKK) developed a family medicinal plant garden (TOGA) whose results can be used for traditional medicine for residents in their area. Medicinal plants are usually prepared from the decoction of fresh ingredients obtained from the TOGA garden. Medicinal plant products must be used immediately to avoid the risk of spoilage, especially when the yield is abundant. One of the technologies to reduce the spoilage of medicinal plant products needs to be made in the form of Simplicia. The dry form of Simplicia can make it easier for the public to standardize the doses of medicinal plants and prepare standardized decoctions using the infusion and decoct methods. The service program aims to increase knowledge and skills in making Simplicia and preparation techniques for traditional red ginger and papaya leaf medicines according to standard dosages. The methods used in implementing the program were tutorials and practices. The results of the service program were as follows: 1) Knowledge of PKK partner women in the Sambiroto and Sendang Mulyo areas, Semarang, quantitatively increased significantly by 13.83% as shown by the results of the pre-test vs. post-test, 69.5 vs. 83.33, p-value 0.034; 2) Knowledge and technical skills for preparing traditional medicines using the infusion and decoct methods also increased significantly.